MUSLIMAH MOMPRENEUR DALAM MAJALAH KELUARGA ISLAM HADILA (Solusi Alternatif Dilema Peran Ekonomi Perempuan dalam Keluarga Sakinah) - Sidik Sidik (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
Women’s dilemma between career and family is one of the prominent discourses on sakinah family development today that needs to solve. This paper analyzes the concept of Hadila Islamic family magazine, as one of the tarbiyah movement representations, on the construction of muslimah mompreneur as a model of women economic role in developing sakinah family. It also analyzes how is its relevancy with the sakinah family regulations in Indonesia and with the theoretical solution for women dilemma in career and family. By using framing analysis, this paper finds that muslimah mompreneur constructed by Hadila is the women as a housewife, having a business around female employment, running a business autonomously or together with her husband, having a business based on professionality and religious values, as well as having some purposes to maximize the role of household, self-empowerment, and independence. Such constructions are relevant to the construction of women economic role in sakinah family regulations in Indonesia. Furthermore, it strengthens women domestication but more flexible where the role of the household can be maximized together with the economic role. It also strengthens a model of women economic role based on religious values as Islamic family identity. By such construction, muslimah mompreneur is different from some theories connected to women dilemma between career and family, as well as give an alternative choice, although it tends to be patriarchal and domestication.